A Secular Variation in the Moon’s Orbit Inclination Supposing the Moon is an Ejected Body: About the Lunar Nodal Point and the Precession Constant - Ciobanu, Monica Zoe (European Journal of Applied Sciences, 2024)
Supposing the Moon as if it has been ejected in a past geological period, the author of this paper analysed the possible variation of the Moon’s orbit inclination, from that moment of possible ejection, until now, in the ecliptic frame of axis. Admitting that the obliquity of ecliptic could be greater in that distant geological past, the author supposes that the inclination of Moon’s orbit related to ecliptic plan could decreased from an abstractly supposed great value (for instance around “40°”) to five degrees now. That could impose the acceptance of a possible secular variation in the Moon’s orbit inclination, related to the ecliptic plan.